Effective management of educational facilities and infrastructure to ensure safe and supportive learning environments - Iqlima, Zsazsa Ghania; Nurjanah, Fitri; Rustini, Tin (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
Effective management of educational facilities and infrastructure is essential for creating safe, supportive, and high-quality learning environments. This article aims to identify key strategies, stages, and best practices in the management of educational infrastructure to enhance the effectiveness of the teaching–learning process. Using a library research approach, this study synthesizes findings from books, academic journals, and other relevant literature to examine the stages, challenges, and solutions associated with facility and infrastructure management in educational institutions. The review reveals that facility management encompasses several systematic stages, including planning, needs analysis, procurement, inventory administration, utilization, storage management, maintenance, disposal, and accountability reporting. Adequate facilities—such as classrooms, laboratories, libraries, and learning media—play a crucial role in improving student motivation, supporting innovative teaching methods, and enabling effective curriculum implementation. However, various challenges hinder optimal management, including limited budgets, policy inconsistencies, inadequate stakeholder participation, and unequal distribution of infrastructure across regions. Proposed solutions include strategic financial planning, investment in sustainable technology, strengthening collaboration with government and community stakeholders, and developing regulatory policies that support efficient infrastructure management. Overall, the study highlights that effective facility and infrastructure management significantly contributes to improving the quality of education by ensuring that students learn in safe, comfortable, and well-supported environments. Strengthening management practices will help educational institutions meet future demands and achieve long-term educational goals.